Tổng quan nghiên cứu về định giá carbon và chuyển đổi khí hậu trong ngân hàng - Nguyễn Đăng, Khoa (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study takes a comprehensive bibliometric approach to the carbon - climate transition in the banking sector. Using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) screening process to ensure the systematicity of the data, the author synthesized 42 main studies from 193 publications in the Scopus database during the period 2010 to 2024. From there, through the VOSviewer tool, the study has identified six emerging research clusters: (1) climate risk assessment, (2) financial system and stability, (3) carbon finance, (4) climate change and transition, (5) banking operations, and (6) policy and regulation. These research trends highlight the diversity of the current field while emphasizing policy implications for the region as well as systemic risk issues. Additionally, the emerging research themes identified from the intersection of topic clusters suggest future directions, highlighting the need for continuous methodological innovation, and practical applications to effectively address climate-related financial risks.
Keywords: Carbon pricing; Climate transition risk; Banking